The origin and development of psychoanalysis - Freud, Sigmund, 1856-1939. (Chicago : Regnery Gateway ; New York : distributed by Kampmann, 1987)
These lectures were delivered by Freud at Clark University in 1940, only one year after his controversial psychoanalytic movement first received public recognition.
Five lectures delivered at Clark University in 1910.
Keywords: Psychoanalysis